CHEMICAL AND ANTIOXIDANT CHARACTERISTICS OF FERMENTED YELLOW PUMPKIN FLOUR WITH VARIATION OF MICROORGANISMS AND FERMENTATION TIME - Sari, Anisa Rachma; Putri, Aldila Sagitaning; Gunantar, Devy Angga (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2024)
Pumpkin flour produced through fermentation can increase its nutritional value. This study aims to analyze the chemical characteristics and antioxidants of fermented pumpkin flour with variations in microorganisms and fermentation time, as well as the correlation between the two factors, and determine the best formulation. This study used a factorial group randomized design method with two factors, namely, variation of microorganism and fermentation time. The data obtained were analyzed using factorial ANOVA, followed by the Duncan Multiple Range Test (DMRT) test with a confidence level of 95% using SPSS 23. The chemical characteristics of fermented pumpkin flour showed an interaction between fermentation microorganisms and the length of fermentation time on the antioxidant activity of fermented pumpkin flour, but there was no interaction between fermentation microorganisms and the length of fermentation time on the moisture content, ash, protein, fat, and carbohydrates of fermented pumpkin flour. Fermentation by S. cerevisiae for 3 days had the best chemical characteristics and antioxidant activity of fermented pumpkin flour. Researchers hope that the application of fermentation in processing pumpkin into flour can increase the nutritional value, the economic value, and the value of health.